Design of novel F-ATP synthase inhibitors of mycobacterium tuberculosis - Hotra, Adam (2018)
F1FO ATP synthase of Mycobacterium tuberculosis is an attractive and intensively-studied drug target. Adenosine triphosphate (ATP) is necessary for cell growth and is vital for cell survival, especially in the case of dormant Mycobacterium. In 2012, an inhibitor of F1FO ATP synthase, Bedaquiline (BDQ) was approved for the treatment of tuberculosis (TB). Despite promising efficacy, BDQ was found to have several adverse effects and therefore is used solely for the treatment of multiple drug-resistant tuberculosis (MDR-TB). This suggests the need for a more viable drug targeting the respiratory chain. A new drug target in F1FO ATP synthase was proposed; a 13 amino acid-long loop γ165–178 at the interface of the c-ring and subunit γ. This loop is unique to Mycobacterium and enables specific compound binding without affecting the human F1FO ATP synthase. To date, no high-definition structure of the Mycobacterium F1FO ATP synthase is present in literature, and hence to study it, a homology model was built. With this model, 1.5 million compounds were docked using Maestro suite (Schrödinger). The 81 best scoring compounds were tested for growth inhibition and one compound (compound 6) inhibited non-pathogenic M. smegmatis with an IC50 11 μM and M. bovis BCG with an IC50 of 40 μM. Furthermore, compound 6 blocked ATP synthesis and hydrolysis in the inverted membrane vesicles assay. Hence, it was confirmed that compound 6 binds to the F1FO ATP synthase as predicted. Additionally, the hydrolysis rate, and amount of ATP synthetized between wild-type vesicles and Δγ166-179 mutant vesicles was compared. Vesicles with the deletion of the γ166-179 loop increased the ATP hydrolysis rate. Interestingly ATP synthesis dropped by 50%. These results suggest that γ166-179 loop plays an important role in the coupling between the c-ring and the central stalk. Moving forward, compound 6 and a series of analogs were synthesized for lead optimization based on the model of the docked compound to the F1FO ATP synthase.